Investigation of saltwater intrusion in the freshwater aquifer and possible ground subsidence near the coastal area of Dagupan City due to excessive groundwater pumping - Rosal, Maria Demi Faye Q.
The increased demand of water corresponds to an increase of groundwater pumping in order to cater the needs of the population of a certain area. Over extraction of which, however, leads to serious consequences such as saltwater intrusion and added information may be obtained such as its effect on ground subsidence. Dagupan City, Pangasinan highly depends on groundwater for their water supply. It is a reclaimed land located near the coast making it highly vulnerable to saltwater intrusion. This study aims to simulate a predictive model of saltwater intrusion in the freshwater aquifers. Additionally, this aims to provide insight on the possible ground subsidence due to excessive groundwater pumping. Simulations were done using FEMWATER of the Groundwater Modeling System (GMS). The data was calibrated and resulted to a difference ranging from 0.1 [m] to 9.92 [m]. Simulations were made for a period of four (4) years or 1460 days with increasing pumping rates of 150% and 200%. The results indicate that saltwater intrusion is a critical concern especially in the pumping stations of Nable, Bonuan Binloc I (JDV), and Perez Market. Hence, it is recommended that certain mitigation measures must be performed to sustain the integrity of the aquifer and maintain the supply capacity of the aquifer.